First asymmetric total synthesis of aspergillide D. Issue 8 (6th February 2017) - Jena, Bighnanshu K.; Reddy, G. Sudhakar; Mohapatra, Debendra K.
Abstract : The first asymmetric total synthesis of aspergillide D was achieved in a longest linear sequence of 18 steps following Sharpless resolution, Yamaguchi esterification, RCM reaction and Shiina macrolactonization. Abstract : The first asymmetric total synthesis of a 16-membered macrolide, aspergillide D, is described. The chiral centers of the acid are derived fromd -ribose and the alcohol subunit from 1, 8-octane diol through Sharpless kinetic resolution, respectively. The other key reactions include Yamaguchi esterification, ring-closing metathesis reaction, and Shiina macrolactonization to construct the fully functionalized macrocycle.